Strategi Pemerintah Daerah Provinsi Jawa Timur Dalam Mewujudkan Program Jatim Bangkit (Riset Deskriptif Kualitatif pada Kampanye Jatim Bangkit)19 - Ufliasari, Rizka (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2023)
All sectors, from micro, medium and small enterprises (MSMEs) to the tourism industry have been affected by the COVID-19 outbreak. Creating micro-scale policies that promote rapid local economic recovery is the primary responsibility of local governments. East Java to continue to be aware of potential threats from the impact of the COVID-19 pandemic, even though the province is described as having good financial system stability in the fourth quarter of October-December 2020. Khofifah Indar Parawansa understands this problem by realizing the "Jatim Bagkit" campaign This online and offline campaign aims to support the activities of MSMEs and the tourism industry during the pandemic. This study uses a qualitative methodology under a descriptive paradigm. This study attempts to describe the implementation of the entire series of "East Java Rise" campaign programs. Based on these findings, many agencies, including the East Java Office of Cooperatives and SMEs, East Java Public Relations, and the East Java Culture and Tourism Office, as well as the East Java Governor's personal Instagram account, are using Instagram content to promote the "Jatim Bangkit" Campaign. This internet effort has also been successful at generating conversation and receiving supportive feedback from the general public. In addition, the "Jatim Bangkit" Campaign was socialized as part of the Rise Tourism program which was carried out offline through the Gowesata event. This campaign is in the form of a bicycle race event from Malang to Bali with the aim of promoting tourism in the destination area.